Application of sensors in automated soilless cultivation of high-value vegetable crops - M. Hasan; Tripathi, A. M.; Kumar, Vinod; Rongali, Mahesh; Kumar, Adarsh (Indian Horticulture, 2025)
Soilless cultivation technology refers to growing high-value horticultural crops in different soilless medium which is totally devoid of soil. It includes grow bag technology, pure hydroponics, aeroponics and aquaponics. Popular soilless growing medium used are cocopeat, perlite, vermiculite, rockwool, cocochip, sand, stonechip etc. in different combinations or alone itself. It is used mainly inside protected structures to grow high-value horticultural crops round the year for maximizing production, productivity, quality and overall income. Currently, it is urgently required mainly inside protected structures to overcome rampant soil borne diseases and nematodes. It is used for efficient water and nutrient management as well as for overall control by modern IT based tools like sensors, automation and IoT. Sensors are commonly used by growers for overall supervision and management of the growing system for high-value vegetables, flowers, spices and greens.